(untitled) (Journal of Comparative & International Higher Education, 2024)
This article explores the rise of digitalisation in Australian higher education and its impact on learning and teaching, administration, and regulatory obligations. This digitalisation can be epitomised by the prevalence of learning management systems (LMS) which have radically reshaped the conduct and configuration of education. As universities have embraced the LMS, as forced by the pandemic, the swelling confluence of disruptive digitalisation combined with globalisation, regulatory reforms, and shifts in government funding models have seen the Australian higher education sector in constant evolution. This article contextualises the impacts of digitalisation using the lens of neoliberalism and globalisation, with past, current, and future state considerations in the sector. It includes a case study from a large metropolitan Australian university with a signature pedagogy of industry-partnered and flexible learning to consider how Higher Education Institutions (HEIs) in Australia must continue to evolve in identity and provision of learning to serve social interests for the future in digitalised contexts.